Marketingová komunikace podniku prostřednictvím Instagramu - Veselá, Marie (Vysoké učení technické v Brně. Fakulta podnikatelská, 2019)
Tato práce se zabývá marketingovou komunikací firmy fyftstore s.r.o. (dále jen Fyft) prostřednictvím sociální sítě Instagram. Firma Fyft vlastní e-shop a kamennou prodejnu v Brně. Jejich produkty podporují volnočasové aktivity, např. yoyo, Rubikovy kostky, deskové hry apod. Práce podává návrh na zlepšení propagace firmy na sociální sítí, vytvořením užitečné publikační šablony. Za dva měsíce naší spolupráce se povedlo zvednout počet sledujících až o 300 a překonat hranici 1000 sledujících.

My thesis analyzes marketing communication of the company fyftstore s.r.o. (hereinafter referred to as Fyft) via a social network called Instagram. The company owns an e-shop and a stone shop in Brno. They sell leisure time products, for example yoyo, rubiks cube, board games etc. This thesis proposes to improve the promotion of the company on the social network by creating a useful publication template. In two months of our collaboration, Fyft managed to gain over 300 new instagram followers and finally reach the „1000 followers milestone.“
Marketing Communication of a Company via Instagram
Keywords: marketing; marketingová komunikace; sociální sítě; dosah; influencer; sledující; marketing; marketing communication; social networks; reach; influencer; follower